Development of New Punch Shape to Replicate Scale‐Up Issues in Laboratory Tablet Press II: A New Design of Punch Head to Emulate Consolidation and Dwell Times in Commercial Tablet Press. Issue 6 (2nd May 2014) - Aoki, Shigeru; Uchiyama, Jumpei; Ito, Manabu
<x xml:space="preserve">Abstract</x> Differences between laboratory and commercial tablet presses are frequently observed during scale‐up of tableting process. These scale‐up issues result from the differences in total compression time that is the sum of consolidation and dwell times. When a lubricated blend is compressed into tablets, the tablet thickness produced by the commercial tablet press is often thicker than that by a laboratory tablet press. A new punch shape design, designated as shape adjusted for scale‐up (SAS), was developed and used to demonstrate the ability to replicate scale‐up issues in commercial‐scale tableting processes. It was found that the consolidation time can be slightly shortened by changing the vertical curvature of the conventional punch head rim. However, this approach is not enough to replicate the consolidation time. A secondary two‐stage SAS punch design and an embossed punch head was designed to replicate the consolidation and dwell times on a laboratory tablet press to match those of a commercial tablet press. The resulting tablet thickness using this second SAS punch on a laboratory tablet press was thicker than when using a conventional punch in the same laboratory tablet press. The secondary SAS punches are more useful tools for replicating and understanding potential scale‐up issues. © 2014 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci